A Formação do professor: um estudo a partir da concepção de ética em Paul Ricoeur - Smarjassi, Célia Marilda [UNESP] (2014)
The teaching practice claims, by essence and vocation, an eminently ethical action, because the teacher gives human form to the values, hence the importance of ethical formation of the teacher, for from this professional is expected a singular posture of being in the world. In this research we are looking to answer the following question: What are the principles and guidelines of the ethical thought of Paul Ricoeur that would provide an adequate analysis of the disposal of the National Curriculum Guidelines for the Graduation Course in Pedagogy, graduation and the National Curriculum Guidelines for the Training of Teachers of Basic Education, in higher education, degree course, full degree around ethics in teacher training? Methodologically this research appears as bibliographic and documentary, therefore theoretical. In conclusion we note that the official guidelines for the training of teacher bring misconception about the ethics conception. We notice that Ricoeur’s standing, about ethical living guides to a life marked by a behavior in which the person is guided by a self-criticism and self-analysis, and is able to assume attitudes consciously and responsibly, therefore we conclude that his thoughts about ethics might be a valuable tool to develop the teacher’s formation